Strategi Dakwah Tokoh Agama Dalam Meluruskan Kepercayaan Masyarakat Terhadap Puyang Semiluan Di Desa Taja Indah Kecamatan Betung Kabupaten Banyuasin - Ariyanto, Ariyanto; Hidayat, Hidayat; Dewi, Emi Puspita (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is entitled "Dakwah Strategy in Upholding Community Trust in Puyang Semiluan Village, Taja Indah Village, Betung District, Banyuasin Regency". The purpose of this study was to find out the da'wah strategies of religious leaders in rectifying the beliefs of the Taja Indah community towards Puyang Semiluan and the challenges of implementing the da'wah strategies of religious leaders in improving public trust in Puyang Semiluan in Taja Indah Village, Betung District, Banyuasin Regency. The method used in this study is a qualitative research method with primary and secondary data sources. Then researchers used data collection techniques through the stages of observation, interviews and documentation. The data analysis technique used in this study uses Miles and Huberman's theory regarding qualitative data analysis which is carried out by the process of data reduction, data presentation, and drawing conclusions. The theory used in this study uses the da'wah strategy theory according to Al-Bayyuni which consists of: 1) sentimental strategy, 2) rational strategy, 3) sensory strategy, and the theory of public trust according to R. Otto. The results of this study discuss the da'wah strategies of religious leaders in straightening out the beliefs of the Puyang Semiluan community in Taja Indah Village, Betung District, Banyuasin Regency, namely: 1) training and coaching for majlis ta'lim, 2) study traditions, 3) involving youth in religious activities. The challenges of implementing da'wah by religious leaders in rectifying the community's beliefs in Puyang Semiluan, Taja Indah Village, Betung District, Banyuasin Regency are: 1) habits that are difficult to change, 2) da'wah that is difficult to accept, 3) lack of knowledge of some people about Islamic teachings.